Класифікація підстав адміністративної відповідальності за порушення законодавства у секторі безпеки України - Цибульник, Н. Ю.; Tsybulnyk, N. Yu. (Věda a perspektivy. - 2023. - № 6(25). - P. 148-159, 2023)
Досліджено підстави адміністративної відповідальності за порушення норм законодавства у секторі безпеки України, сформовано їх класифікацію. Розглянуто проблематику тлумачення поняття «адміністративної відповідальності» на підставі нормативних визначень та доктринальних поглядів. З’ясовано, що поняття «сектор безпеки» включає в себе більше аспектів суспільного життя, аніж нормативно закріплене поняття «сектор безпеки і оборони». Запропоновано поділ адміністративних правопорушень у секторі безпеки на 3 групи: правопорушення у сфері громадського порядку; правопорушення у сфері державної та військової безпеки; правопорушення, пов’язані з соціально-економічною та політичною безпекою.

The article is devoted to the study of existing and the formation of a new classification of the grounds of administrative responsibility for violations of legislation in the security sector. The author considered the problems of interpretation of the concept of "administrative responsibility" on the basis of normative definitions and doctrinal views. It is found that the concept of "security sector" includes more aspects of public life than the normatively established concept of "security and defense sector", and the opinions of domestic and international doctrine on this issue are outlined. Attention is focused on two existing classifications of grounds for administrative liability, among which. Thus, in his writings, V. Kolpakov proposed 3 reasons that found support among domestic scientists: actual normative and procedural. This classification has found its support among scientists and is now quite actively used in various studies. Another well-known classification is the division also into three groups of grounds: material and legal; administrative and procedural; organizational The author proposed dividing administrative offenses in the security sector into 3 groups: offenses in the sphere of public order; state and military offenses; socio-economic and political offenses. It has been investigated that employees of police bodies, as well as military personnel, are responsible for administrative offenses under disciplinary statutes. The provisions of the Code of Ukraine on administrative offenses and scientific works were analyzed, according to which it was determined that despite the fact that there is no administrative sanction in this case, such an offense does not cease to be administrative. The issue of state and military security was investigated within the framework of the Law of Ukraine "On National Security of Ukraine", as well as in view of the work of the Armed Forces of Ukraine, the Security Service of Ukraine, the National Bank of Ukraine, as well as the National Anti-Corruption Bureau of Ukraine.

Исследованы основания административной ответственности за нарушение норм законодательства в секторе безопасности Украины, сформирована их классификация. Рассмотрена проблематика толкования понятия «административной ответственности» на основании нормативных определений и доктринальных взглядов. Установлено, что понятие «сектор безопасности» включает в себя больше аспектов общественной жизни, чем нормативно закрепленное понятие «сектор безопасности и обороны». Предложен раздел административных правонарушений в секторе безопасности на 3 группы: правонарушения в сфере общественного порядка; правонарушения в сфере государственной и военной безопасности; правонарушения, связанные с социально-экономической и политической безопасностью.
Classification of grounds of administrative liability for violations of legislation in the security sector of Ukraine
Keywords: адміністративне правопорушення; administrative offence; административное правонарушение; сектор безпеки України; security sector of Ukraine; сектор безопасности Украины; адміністративна відповідальність; administrative responsibility; административная ответственность; класифікація підстав; classification of grounds; классификация оснований